All hell breaks loose: Supernatural, gothic neoliberalism and the American self. Issue 2 (1st October 2015) - Blake, Linnie
Chronicling the power-struggles of angels and demons drawn broadly from the Judaeo-Christian tradition and deploying a cast of vampires, ghosts, demons, shapeshifters, tricksters, mad scientists, zombies and monsters from urban legends, the TV gothic serial Supernatural is both a quintessentially American narrative and a sustained critique of the internal contradictions of neo-liberalism. Revelling in the mass cultural products of the United States, it incorporates the generic characteristics of the western, the road movie and the mystery-thriller whilst evoking the formats of the serial novel, the game show, the police procedural, reality television and gothic film and television. Thus addressing the epistemological incertitude engendered by the 'grave economic distress' (4:17) of the present, Supernatural charts the disjunction between public fantasies of free market freedoms and the trauma wrought to social and psychological integrity by industrial decline and community breakdown. What emerges is a terrifying picture of a country that has been plunged into existential chaos by neo-liberal economics. In the world of Supernatural, as in our own, exceptionalist models of national identity have been dismantled, compromised or exposed as ideologically expedient fantasies, whilst their neo-liberal substitutes have made both the self and the socius unstable, fragmented and mutable. Freedom, the protagonist Dean Winchester argues, is simply the rope God gives people to hang themselves (6.20), in the certainty that hang themselves they will. Meantime the brothers inhabit a world in which, it is frequently reiterated, both justice and liberty are nothing more than abstract concepts, the rule of law has become irrelevant and the power of the powerful knows no bounds whatsoever. Across ten seasons, therefore, the Winchester brothers cross and re-cross not only the American landmass but a series of temporal, ethical, epistemological and ontological frontiers. In so doing, they undertake a highly gothic interrogation of what it means, in the age of neoliberal corporatism, to be both 'an American' and a man.